PEMERTAHANAN BAHASA DAN TRADISI MELALUI PELESTARIAN KESENIAN TOGAL MANIKA SUKU MAKEAN MALUKU UTARA - Hi Muhammad, Hujaefa; Abdullah, Wakit (Hasta Wiyata, 2018)
Language maintenance need to be done for the sake of non-existant languages. The extinction of language influences of local wisdom and make disappearance of the nation's assets. One way can be done is to preserve togal manika: a combination of music, dance, and song. This art comes from the island of Makean with the terms Makean Luar and Makean Dalam in North Maluku. This study explain (1) Diglosi that occurs in the Island of Makean, North Maluku, and explain (2) efforts to preserve the language of togal manika. Data collection using observation and interview. The results of the study found that (1) diglossia was occurred in Low Language in the familial sphere kinship, neighborhood, and friendship. In Higher Language, diglosi was occured in all domains: education, government, religion. Efforts to preserve the language of the Togal Manika are done in ways: (1) celebration at people’s party (2) Government support(3) Disk through recording Compact Disk, (4) Social media, (5) Competition event, (6) Extracurricular in school , (7) government and campus events, and (8) publication of articles, publications in the media, and research related to local wisdom togal manika.